An Optimization Model for the Electricity Market Clearing Problem With Uniform Purchase Price and Zonal Selling Prices - Savelli, Iacopo; Giannitrapani, Antonio; Paoletti, Simone; Vicino, Antonio (IEEE transactions on power systems, 2018)
Electricity markets can be designed in different ways. One rule that is sometimes enforced is the uniform purchase price. Under this pricing method, all the consumers pay the same price regardless of the zone they belong to. By contrast, each producer receives its zonal price. This asymmetry in the price paid and received makes the clearing process not easily treatable through standard optimization techniques. Within the framework of marginal pricing, this paper shows how it is possible to formulate the market clearing problem with uniform purchase price and zonal selling prices as a computationally tractable mixed integer linear programming problem. The proposed approach is tested using real data from the Italian day-ahead market, which is actually based on the aforementioned rule.